2020
DOI: 10.1186/s13287-020-01995-y
|View full text |Cite
|
Sign up to set email alerts
|

Autologous adipose-derived stem cells for the treatment of complex cryptoglandular perianal fistula: a prospective case-control study

Abstract: Background Complex cryptoglandular perianal fistula (CPAF) is a kind of anal fistula that may cause anal incontinence after surgery. Minimally invasive surgery of anal fistula is constantly emerging. Over the past 20 years, there are several sphincter-sparing surgeries, one of which is autologous adipose-derived stem cell (ADSC) transplantation. However, to date, there is no study regarding the treatment of complex CPAF with ADSC in China. This is the first study in China on the treatment of complex CPAF with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The description of healing is clinical, with some differences when Magnetic Resonance is used. In some trial we observed a success in more than of 70% of patients ( 22 , 24 , 27 ), but with fewer patients this rate of healing suddenly decreases ( 28 , 29 ), also for the learning curve. Complications are frequent, even if major adverse events are rare and with an easy resolution: most common are perianal abscess especially at the beginning of the experience ( 27 ).…”
Section: Results Of Ascs In Cryptoglandular Anal Fistulamentioning
confidence: 90%
See 1 more Smart Citation
“…The description of healing is clinical, with some differences when Magnetic Resonance is used. In some trial we observed a success in more than of 70% of patients ( 22 , 24 , 27 ), but with fewer patients this rate of healing suddenly decreases ( 28 , 29 ), also for the learning curve. Complications are frequent, even if major adverse events are rare and with an easy resolution: most common are perianal abscess especially at the beginning of the experience ( 27 ).…”
Section: Results Of Ascs In Cryptoglandular Anal Fistulamentioning
confidence: 90%
“…Recently, the use of ASCs was compared not only with fibrin glue but also with other surgical techniques, such as endorectal (29). A phase I trial shows an association with a different technique for the closure of fistula tracts, the anal plug: 15 patients with trans-sphincteric cryptoglandular fistulas received a MSC-loaded fistula plug, with complete healing reported in three and "partial" in 7 (28).…”
Section: Results Of Ascs In Cryptoglandular Anal Fistulamentioning
confidence: 99%
“…67 Data from clinical trial studies for the treatment of fistula using ASCs are reported in Table 1. [75][76][77][78][80][81][82][83][84][85][86][87][88]…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Local injection of adipose tissue-derived mesenchymal stem cells (AT-MSCs) has emerged as a novel approach with promising outcome in the treatment of both cryptoglandular fistulas and fistulizing Crohn’s disease [ 8 , 9 ]. A variety of approaches have been reported including the use of cultured autologous stem cells [ 10 ] or in vitro expanded allogenic AT-MSCs that showed in a large phase 3 clinical trial, 50% in intervention compared to 30% healing rate of anal fistulas in patients with Crohn’s disease in the control group at 24 weeks follow up [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of approaches have been reported including the use of cultured autologous stem cells [ 10 ] or in vitro expanded allogenic AT-MSCs that showed in a large phase 3 clinical trial, 50% in intervention compared to 30% healing rate of anal fistulas in patients with Crohn’s disease in the control group at 24 weeks follow up [ 11 ]. Other clinical studies reported a positive effect of using autologous AT-MSCs on a closure rate (around 50%) in the patients with cryptoglandular perianal fistulas in short and long term follow up period using different techniques and concentration of stem cells [ 9 , 12 ]. However, these cell products require laboratory facilities to isolate and expand the cells in vitro and manufacturing the product is time consuming and very expensive.…”
Section: Introductionmentioning
confidence: 99%